Universities and entrepreneurship : meeting the educational and social challenges - Jones, Paul, 1967 September 22-; Apostolopoulos, Nikolaos; Kakouris, Alexandros; Moon, Christopher; Ratten Vanessa; Walmsley, Andreas (Contemporary issues in entrepreneurship research ;, 2021)
Universities and Entrepreneurship: meeting the educational and social challenges addresses the concerns on how universities nurture entrepreneurship and how this leads to their transformation into entrepreneurial universities. This novel edited volume attempts to answer the following timely questions: 1.What are intrinsic demands for entrepreneurship rooted to universities in the 21st century? 2.What are conducive environments for entrepreneurial learning in both academic and non-academic settings? 3.Do these attempts demonstrate differential impact across students from different disciplines, and more generally amongst the youth population? This eleventh volume of Contemporary Issues in Entrepreneurship Research is a valuable contribution to the intersection of research into entrepreneurship education and entrepreneurial universities. In acknowledging the varied and somewhat piecemeal approach taken to address these issues to date, this edited volume provides a more systematic and integrated perspective with relevance for students of entrepreneurship as well as for educators and policymakers.